Pertambangan Emas Tanpa Izin di Kalimantan Barat: Kajian terhadap Penegakan Hukum dan Dampak Sosial Ekonomi - Reinhard Halomoan Sagala; Gusti Eka Suhendra; Muhammad Iqbal Nasution; Nafsiatun (CV Global Research Publication, 2026)
This study examines illegal gold mining (PETI) activities in West Kalimantan Province from a normative legal perspective and its socio-economic impacts on the community. The prevalence of illegal gold mining is influenced by limited employment opportunities, low levels of public education, high gold prices, and the difficulty of accessing official mining permits. This study uses a normative legal method with an approach based on legislation, legal doctrine, and relevant literature. The results show that illegal gold mining constitutes an unlawful act as regulated in Article 158 of Law Number 3 of 2020 concerning Mineral and Coal Mining, which regulates criminal sanctions for perpetrators of illegal mining. Law enforcement is carried out through preventive and repressive efforts, but its implementation still faces obstacles such as the vastness of the mining area, limited apparatus, and the involvement of certain parties who profit from this illegal activity. On the other hand, illegal gold mining has a positive economic impact in the form of increased income and employment, but it also has negative impacts in the form of environmental damage, river pollution, social conflict, and the loss of potential state revenue. Therefore, a comprehensive policy is needed through strengthening supervision, simplifying licensing, and empowering the community economy.